Troponin T release is associated with silent myocardial ischaemia in black men: The SABPA Study. (June 2017) - Griffiths, Madelein E; Malan, Leoné; Delport, Rhena; Cockeran, Marike; Reimann, Manja
Background: High sensitivity cardiac troponin T (hs-cTnT) is a validated marker of myocardial damage and may reflect the degree of silent myocardial ischaemia (SMI) and ventricular strain. Our aim was to compare hs-cTnT levels in black and white South Africans taking SMI into consideration. We further explored the capability of hs-cTnT to predict the presence of compensatory systolic hypertension in this South African cohort. Methods: A bi-ethnic sex cohort ( n  = 404) with similar socioeconomic status (198 black participants and 206 white participants, aged 20–65 years) participated in this target population study where 24 h ambulatory blood pressure, electrocardiogram and overnight fasting cardiometabolic variables were measured. Results: Hypertension, higher glycated haemoglobin levels and more frequent and longer SMI events were observed more often in the black participants. Multivariate linear regression analysis showed positive associations between SMI events [Adj. R 2  = 0.19; β 0.35 (0.08–0.62); p  < 0.01], SMI event maximum duration [Adj. R 2  = 0.17, β 0.43 (0.16–0.70), p  < 0.01], SMI total duration [Adj. R 2  = 0.12; β 0.37 (0.10; 0.65), p  = 0.05] and hs-cTnT in black males only.] A lower hs-cTnT cut-point ≥4.2 pg/ml for 24 h systolic hypertension was predicted in the black participants compared with ≥5.6 pg/ml in the white participants (area under the curve 0.66–67 (95% CI: 0.57–0.75), p  < 0.001) with a respective sensitivity/specificity of 64/68% and 61/71%. Conclusions: hs-cTnT may be a potential marker of SMI in the prediction of systolic blood pressure increases, as well as clusters of risk factors for cardiovascular disease. Ethnic- and possibly sex-specific references values for hs-cTnT should be considered for risk stratification.